A Tentative Set of Broad Accounting Principles for Business Enterprises (Book). - Littleton, A. C.; Zeff, Stephen A. (The Accounting Review, 1963)
Reviews the book "A Tentative Set of Broad Accounting Principles for Business Enterprises," by Robert T. Sprouse and Maurice Moonitz.